2022
DOI: 10.3389/fphys.2022.1031519
|View full text |Cite
|
Sign up to set email alerts
|

Circadian clock—A promising scientific target in oral science

Abstract: The oral and maxillofacial organs play vital roles in chewing, maintaining facial beauty, and speaking. Almost all physiological processes display circadian rhythms that are driven by the circadian clock, allowing organisms to adapt to the changing environment. In recent years, increasing evidence has shown that the circadian clock system participates in oral and maxillofacial physiological and pathological processes, such as jaw and tooth development, salivary gland function, craniofacial malformations, oral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 126 publications
(169 reference statements)
1
18
0
Order By: Relevance
“…It was reported that complete SCN lesions result in the disappearance or disturbance of daily growth lines in rat incisors 15 . In addition, an increasing number of clock genes, such as Bmal1, Clock, Per, and Cry, have been reported to be expressed in tooth germs 20,37,53 . These studies further con rm the effects of the circadian rhythm on tooth development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that complete SCN lesions result in the disappearance or disturbance of daily growth lines in rat incisors 15 . In addition, an increasing number of clock genes, such as Bmal1, Clock, Per, and Cry, have been reported to be expressed in tooth germs 20,37,53 . These studies further con rm the effects of the circadian rhythm on tooth development.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of these incremental growth lines suggests that dentin/enamel formation and maturation are under circadian control. Several studies 15,19,20 have reported that the clock genes Bmal1, Clock, Per, and Cry are detected in different stages during tooth development and oscillate at regular 24-hour intervals. Moreover, several odontogenesis-related factors (e.g., ameloblastin, amelogenin, and lysosomeassociated membrane protein) have been reported to exhibit regular oscillating expression patterns in rat tooth germs at postnatal day 1 (PN1) 5,21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…A decreased quantity or quality of saliva can increase the risk of dental caries [ 50 ]. Saliva is essential for regulating the oral microbiome and maintaining oral health, especially in preventing oral diseases and controlling oral infections [ 51 ]. Normal saliva secretion and saliva flow are directly related to oral health.…”
Section: Dental Cariesmentioning
confidence: 99%
“…Normal saliva secretion and saliva flow are directly related to oral health. Decreased saliva flow is an important indicator of oral health, and disorders of the salivary glands are the main factor affecting the decrease in saliva flow [ 51 ]. Saliva has the most significant influence on caries’ progression [ 52 ].…”
Section: Dental Cariesmentioning
confidence: 99%
See 1 more Smart Citation